A flux-based assessment of above and below ground biomass of Holm oak (Quercus ilex L.) seedlings after one season of exposure to high ozone concentrations. (July 2015) - Gerosa, Giacomo; Fusaro, Lina; Monga, Robert; Finco, Angelo; Fares, Silvano; Manes, Fausto; Marzuoli, Riccardo
Abstract: Young plants of Holm oak ( Quercus ilex ) were exposed in non-limiting water conditions to four different levels of ozone (O3 ) concentrations in Open-Top Chambers during one growing season to evaluate biomass losses on roots, stems and leaves in relation to O3 exposure (AOT40) and phytotoxical ozone dose (POD1 ) absorbed. The exposure-effect and dose-effect relationships for the total biomass were statistically significant and indicated a reduction of 4% and 5.2% of the total biomass for each increase step of 10000 ppb h of AOT40 and 10 mmol m −2 of POD1, respectively. The results indicate a critical level for Holm oak protection of 7 mmol m −2 of POD1, which corresponds to 4% of total biomass reduction. The linear regressions based on the POD1 were significant for roots and stem biomass losses, but not significant for leaf biomass. The biomass loss rate at increasing POD1 was higher for roots than for stems and leaves, suggesting that stem growth under high levels of O3 is less affected than root growth. Because of the scarcity of data from the Mediterranean area, these results can be relevant for the O3 risk assessment models and for the definition of new O3 critical levels for forests in Europe. Highlights: Ozone dose–response relationships for biomass losses of young Holm oak trees are presented. Stem growth of Holm oak under high levels of O3 is less reduced than roots. Holm oak showed an O3 sensitivity between deciduous broadleaved and evergreen coniferous species.